Diels and his attitude towards the history of ancient Greek philosophy. About an unpublished and very brief text by Walter Burkert - Marcio Cid, Ignacio (Anales del Seminario de Historia de la Filosofía, 2023)
The aims of this article are twofold: 1) to elaborate, on the occasion of the first centenary of his death, a brief bio-bibliographical note about Hermann Diels in order to highlight again his figure and contributions to the history of pre-Socratic philosophy; 2) to clarify what was his main orientation regarding Greek antiquity, be it of philological, philosophical or scientific-technical nature; 2.1) to provide evidences showing his position on that matter, by drawing on various sources of information, which include the published transcription of his lectures on the history of ancient Greek philosophy and also by disclosing a short and unpublished text in which the late Walter Burkert, an expert on the Hellenic world and on Diels himself, assesses the merits of the above mentioned transcription and of Diels as historian of ancient Greek philosophy.